Are Academics Driven by Managerialism? Governance and the Changing Role of Academics on the Way Towards a Knowledge Society - Teichler, Ulrich (Acta Paedagogica Vilnensia, 2021)
Changes in the governance system have been viewed as one of the key issues of higher education since about the 1990s. In many countries, the “managerial university” emerged accompanied by a controversial discourse about its strengths and about dangers implied. As academics are key actors performing key functions in higher education and as governance reforms increased the power of university management to steer academics, the academics’ perception of and response to the “managerial university” is crucial for its successes and failures. International comparative surveys of academics undertaken in the early 1990s and during the years 2007-2010 indicate that the modes of governance and the responses to these modes by academics vary more substantially across countries than the convergent international discourse suggests. Altogether, scholars’ views and behavior seem to have changed to a lesser extent than expected. The third comparative survey of that kind addresses similar issues, but additionally raises the question of whether strong footprints can be observed of the move toward a “knowledge society” with regard to the governance of higher education and academics’ views and activities.
Keywords: governance in higher education; university management; academic profession; knowledge society